PENGARUH REPUTASI AUDITOR DAN AUDIT TENURE TERHADAP KUALITAS AUDIT (Media Riset Akuntansi, 2022)
This study aims to measure and analyze the influence of auditor’s reputation and audit tenure on audit quality (empirical study on manufacturing companies listed on the Indonesia Stock Exchange period 2014-2016). The dependent variable used in this study is audit quality. The independent variables used in this study are auditor reputation and audit tenure. The populations used in this study are all companies engaged in the Indonesia Stock Exchange in 2014 until the year 2016 in a row. Technique of data retrieval is done by using purposive sampling method; data obtained as many as 177 samples that meet the criteria. Data analysis method used in this research is quantitative approach by using logistic regression. Secondary data is obtained from annual reports of manufacturing companies listed on the Indonesia Stock Exchange. Based on the research that has been done on manufacturing companies listed in Indonesia Stock Exchange, it can be concluded that the auditor's reputation has an effect on the quality of audit. while audit tenure does not affect on audit quality.